Cropping systems and previous crops on soil density and survival of soil‑borne pathogens - Toledo-Souza, Eliane Divina de; Silveira, Pedro Marques da; Junior, Murillo Lobo; Filho, Adalberto Corrêa Café (Pesquisa Agropecuaria Brasileira, 2008)
The objective of this work was to evaluate the effect of cropping systems and crops cultivated previously to common beans (Phaseolus vulgaris L.) on soil density and soil populations of Rhizoctonia spp. and Fusarium spp. Previous crops included the following legumes: Cajanus cajan, Stylosanthes guianensis cv. Mineirão and Crotalaria spectabilis; and the following grasses: Pennisetum glaucum (cv. BN-2, millet), Sorghum bicolor (cv. BR 304), Panicum maximum cv. Mombaça, Brachiaria brizantha cv. Marandu and a consortium of corn (Zea mays) and B. brizantha. Previous crops were planted in Brazil summer seasons (wet) of 2002, 2003 e 2004, and bean crop (cv. BRS Valente) was planted in the correspondent subsequent winters (dry) of 2003, 2004 and 2005, irrigated by central pivot. Crop residues were incorporated to the soil, in conventional tillage, and kept on the surface, in no tillage management. In general, soil populations of Fusarium spp. and Rhizoctonia spp. were higher in no tillage cropping system. Higher populations of Rhizoctonia spp. were found in heavier soils. Legume crop residue increased soil populations of Rhizoctonia spp. and Fusarium spp. and, therefore, Leguminosae should be avoided as previous crops to common beans, in both cultivation systems. Generally, Gramineae previous crops are supressive to soil populations of Rhizoctonia spp. and Fusarium spp.